Analysis of International Monetary Fund and Islamic Financing in Nigeria: the Better Development Financing Options - Okeokwo, Thankgod; Linus, Gadzama Christopher (International Journal of Law Analytics, 2024)
The motivation for this research is an appraisal of the Laws Relating to the International Monetary Fund and its Impact on the Economic Development of Nigeria as well as the possibilities of Islamic Financing as an alternative to the International Monetary Fund. The objectives of the research include to analyze the legal and institutional frameworks for International Monetary Fund and those for Islamic financing; examine the role of International Monetary Fund in the development of member countries; extrapolate Islamic Banking potentials for economic development of Nigeria; and, analyze the IMF, Nigeria economic development partnerships and Islamic Banking model for development. The research adopted a doctrinal method and consulted primary and secondary sources such as the Articles of Agreement of International Monetary Fund, Banks and Other Financial Institutions Act, Companies and Allied Matters Act; then, journals articles and books. The research found that the IMF lends money to nurture the economies of member countries within balance of payments problems instead of lending to fund member's growth/development infrastructure projects; The IMF expects the countries to pay back the loans with interest, and the countries must embark on structural adjustment policies monitored by the IMF. It was recommended that Nigeria shift from borrowing from IMF to Islamic financing because Islamic financing by its nature is non-interest financing thus making it more convenient for the economic conditions of Nigeria. The research is novel and combines discourse on IMF and Islamic financing for Nigerian economic development.